Immobilization of Isolated Lipase From Moldy Copra (Aspergillus Oryzae) - Seniwati Dali; A. B. D. Rauf Patong; M. Noor Jalaluddin; Pirman; Baharuddin Hamzah (E-Journal of Chemistry)
Enzyme immobilization is a recovery technique that has been studied in several years, using support as a media to help enzyme dissolutions to the reaction substrate. Immobilization method used in this study was adsorption method, using specific lipase from Aspergillus oryzae. Lipase was partially purified from the culture supernatant of Aspergillus oryzae. Enzyme was immobilized by adsorbed on silica gel. Studies on free and immobilized lipase systems for determination of optimum pH, optimum temperature, thermal stability and reusability were carried out. The results showed that free lipase had optimum pH 8,2 and optimum temperature 35 °C while the immobilized lipase had optimum 8,2 and optimum temperature 45 °C. The thermal stability of the immobilized lipase, relative to that of the free lipase, was markedly increased. The immobilized lipase can be reused for at least six times.